PERBANDINGAN MOTEDE KONVENSIONAL EKSTRAKSI PEKTIN DARI KULIT BUAH PISANG DENGAN METODE ULTRASONIK - Adhiksana, Arief (Universitas Nahdlatul Ulama Sidoarjo, 2017)
The Banana is the most widely produced fruit in Indonesia with waste of banana peel about 1/3 of the fruit. If the banana peel is not utilized in large quantities it will cause environmental problems and is a waste of resources because the waste can still be utilized. The Banana peel contains a variety of compounds such as pectin 10-21%. Based on its content, banana peels have potential as a source of pectin. Pectin can be utilized in various industries of making jelly, jam, gelling, thickener, stabilizer andemulsifier. The purpose of this study was to find the influence of ultrasonic and mass on pectin yield. This research was conducted by using ultrasonic method extraction using 0.05 N HCl solvent of 400 mL and extraction temperature of 60 oC. variation of mass in this research are 5, 10, 20, 30 and 40 grams. The highest yield obtained in ultrasonic method is 20.0008 gram with yield of 25,59%. The conventional method only can reach 18,3%.